2015
DOI: 10.1016/j.childyouth.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the self-expressed unmet needs of emancipated foster youth over time

Abstract: a b s t r a c tThis study explores the self-reported unmet need for independent living services of young people making the transition to adulthood from foster care after the creation of the Chafee Foster Care Independence Program. We find that 34.5% of youth indicated that they had an independent living service need that went unmet at age 17, 27.9% at age 21 and 35.5% at age 23, with the largest percentage indicating they lacked preparation in the area of finance. Some of these youth expressed unmet need consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Young people ageing out from foster care have to deal with more issues and take on more responsibility than other young people of the same age. Leaving care research focuses on the transition from leaving care at 18 to independent living; this is usually studied up to 20 to 22 years of age (Biehal & Wade, 1996;Hiles, Moss, Wright, & Dallos, 2013;Höjer & Sjöblom, 2010, 2014Katz & Courtney, 2015;McMahon & Fields, 2015;Singer & Cosner Berzin, 2015;Singer, Cosner Berzin, & Hokanson, 2013;Stein & Dumaret, 2011;Wade, 2008). Follow-up studies of children with experiences of out-of-home care are very rare beyond the age of 25, especially concerning the adult children's relationship to their parents.…”
Section: Glimpses From Other Research On Relationships To Parentsmentioning
confidence: 99%
“…Young people ageing out from foster care have to deal with more issues and take on more responsibility than other young people of the same age. Leaving care research focuses on the transition from leaving care at 18 to independent living; this is usually studied up to 20 to 22 years of age (Biehal & Wade, 1996;Hiles, Moss, Wright, & Dallos, 2013;Höjer & Sjöblom, 2010, 2014Katz & Courtney, 2015;McMahon & Fields, 2015;Singer & Cosner Berzin, 2015;Singer, Cosner Berzin, & Hokanson, 2013;Stein & Dumaret, 2011;Wade, 2008). Follow-up studies of children with experiences of out-of-home care are very rare beyond the age of 25, especially concerning the adult children's relationship to their parents.…”
Section: Glimpses From Other Research On Relationships To Parentsmentioning
confidence: 99%
“…This speaks to the importance of the adult teaching independent living skills. Previous research has found that over a quarter of youth emancipating from child welfare expressed that their independent living needs were not met (Katz and Courtney 2015). Quality independent living programs should take into consideration that youth who are emancipating will be facing challenges that they may not have considered or be aware of (i.e., finances, social support, overall independence).…”
mentioning
confidence: 99%
“…Collins, Spencer, et al, 2017), fewer reports of unmet needs in areas such as employment and housing (e.g. Katz & Courtney, 2015), and increased motivation to pursue post-secondary education (Neal, 2017). To address these concerns, numerous programs and interventions have been enacted on state and federal levels (Stott, 2013).…”
Section: Issues and Concerns Related To The Aging Out Processmentioning
confidence: 99%